Coriander, Coriandrum sativum L. - Diederichsen, A.; Leibniz Institute of Plant Genetics and Crop Plant Research; International Plant Genetic Resources Institute (1996)
A large part of this book describes the genetic resources and variation of coriander and there is also information on uses, composition and crop production. Chapters cover the following topics: taxonomy and names of the species; brief description of the crop; origin of the species and centres of diversity; composition and uses (including for essential oils and fatty oils, and as a medicine, spice and vegetable); genetic resources; diversity of the species; conservation techniques and methods used in ex situ collections; breeding; ecology and agronomy; diseases and insect pests; areas of production and consumption; prospects for research, conservation and development of coriander; and crop limitations and prospects. Particular attention is drawn to publications on the breeding and genetic resources of coriander that were published in the former Soviet Union and have gone unnoticed in western countries. There is an appendix giving addresses of individuals and institutes working with coriander. Much of the basic material used in compiling this book was provided by the germplasm collection of the Gatersleben Genebank in Germany. (Abstract © CAB ABSTRACTS, CAB International)